Investasi Halal dalam Asuransi: Konsep dan Aplikasi - Nabila, Sri Nurul; Hafid, Eka Arlinda; Muchlis, Saiful (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Shariah insurance (takaful) is a system of protection based on Shariah principles that advances cooperation (tabarru’) and avoids usury, gharar (uncertainty), as well as maisir (gambling). This study analyzes the concepts, principles, and developments of Shariah insurance in Indonesia with the method of library research through the study of literature from various sources. Study results show that Shariah insurance is divided into two main types, namely life insurance and general insurance, which operate based on eight main principles: monotheism, justice, helpfulness, trust, voluntariness (‘an taradhin), as well as the avoidance of riba, gharar, and maisir. In Indonesia, the Shariah insurance industry is experienceing significant growth with contributions reaching Rs11.55 trillion in 2021 and projected assets of Rs50 trillion by 2024, supported by OJK regulation and a majority Muslim population. However, the market penetration is still low (5%), indicating a huge development potential. The digitization and spin-off of Shariah enterprise units is a key driving factor in strengthening the national Shariah insurance ecosystem.